PERAN HUMAS MENGEDUKASI MASYARAKAT TENTANG PENTINGNYA ALAT X-SMOKE DALAM MEMERANGI PERUBAHAN IKLIM DAN DAMPAK KARHUTLA - Madinatul Munawaroh (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of this study is to determine the role of public relations in educating the public about the importance of X-Smoke tools in fighting climate change and the impacts of forest and land fires and the media that can be used to support the educational process. Public relations has the most important role in an institution and is the spearhead or forefront of the institution. Public relations in carrying out its role using publication media. This research was conducted using descriptive methods. The data that has been collected from the literature review will then be used as a basis for conducting an analysis. Data analysis was performed using qualitative descriptive. The source of data obtained through a literature study is to use the object of study from books, scientific articles, journals, and literature from the internet that are relevant to the discussion of the problem. The result of this research shows that public relations have an important role in the institution, namely as an expert advisor, communication facilitator, problem-solving facilitator, and communication technician. Publication media that can be used are print, electronic and social media.Keywords: education, the role of public relations, climate change, media publicationTujuan penelitian ini adalah untuk mengetahui peran humas mengedukasi masyarakat tentang pentingnya alat X-Smoke dalam memerangi perubahan iklim dan dampak karhutla dan media yang dapat digunakan dalam menunjang proses memberikan edukasi. Humas memiliki peranan terpenting dalam sebuah lembaga dan menjadi ujung tombak atau garda terdepan dalam lembaga. Humas dalam menjalankan peranannya menggunakan media publikasi. Penelitian ini dilakukan dengan menggunakan metode deskriptif. Data yang telah terkumpul dari hasil tinjauan pustaka selanjutnya akan digunakan sebagai pijakan dalam melakukan analisis. Analisis data dilakukan dengan menggunakan deskriptif kualitatif. Sumber data yang diperoleh melalui studi pustaka yaitu dengan menggunakan obyek kajian dari buku, artikel ilmiah, jurnal maupun literatur dari internet yang relevan dengan pembahasan masalah. Hasil penelitian dapat diketahui bahwa humas memiliki peranan penting dalam lembaga yakni sebagai penasehat ahli, fasilitator komunikasi, fasilitator pemecahan masalah dan teknisi komunikasi. Media publikasi yang dapat digunakan yakni media cetak, elektronik dan media sosial.Kata Kunci: edukasi, peran humas, perubahan iklim, media publikasi